Upaya Mengangkat Camilan Jadul Sebagai Potensi Lokal Desa Cukurgondang Pasuruan - Erwantiningsih, Eni; Wahyuni, Hari; Ariesta, Wiwin (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Processing of the results of farming in Cukurgondang Village into various old school snacks so far is still done manually with thin plastic packaging and does not yet have a business license, so that the production has not been able to penetrate consumers widely. The purpose of this service is to provide assistance in the form of a sealing press machine that can help workers package products neatly and make labels on products to make them attractive and informative in the market. In addition, this service also helps obtain business permits so that MSMEs have the means to participate in programs launched by the government in the future, both training and the possibility of providing business assistance. The method is by surveying locations and markets, procuring press machines and making product labels, managing business licenses, handing over equipment and product labels as well as business license certificates, then machine operation training and providing insight regarding the benefits of obtaining a business license. The object of service is the craftsman of various old school snacks "Bu Cuplik", Cukurgondang Village, Pasuruan Regency. The contribution results show that after improving the quality and appearance of the packaging, it is able to attract consumer interest and have the opportunity to be marketed to outlets and stores.